A High Gain DC-DC Converter Based on Coupled Inductor and Switched-Capacitor Cell with Low-Voltage Stress. (25th May 2022) - Javaheri Fard, Hamed; Sadeghzadeh, Seyed Mohammad
Abstract : This paper presents a nonisolated ultrahigh step-up DC-DC converter with an interleaved structure that is suitable for high power and voltage applications. In order to increase the voltage gain, the proposed structure uses coupled inductors and switched-capacitor cells. Achieving this goal is accompanied by avoiding the imposition of any extreme duty cycle or high turns ratio to the converter. The current ripple is reduced due to the use of the interleaved structure. Since the voltage stress of the switches is lower than the output voltage, by selecting the low-voltage rated switches and small RDS(on), the conduction losses are reduced. In addition, alleviating the phenomenon of reverse recovery of diodes and creating soft-switching conditions in MOSFETs, which leads to a reduction of switching losses, are other advantages of the proposed converter. Therefore, there is no need to use clamp circuits in the mentioned structure. The experimental results, using a prototype of 350 W-18 V/400 V, verify the effective performance of the proposed converter.